Beyond handshakes: - Juliet J. Fall (Revue de Géographie Alpine)
The personal and institutional complications of planning across a larger geographic entity are often poorly understood, and the existing geographical literature reveals a lack of coherent and operative conceptual frameworks for discussing transboundary cooperation as a social and spatial practice of identity construction. This paper briefly describes existing literature on transboundary cooperation, in particular institutional approaches, in order to indicate its inherent limitations. Instead, it suggests that taking the rationales and positionalities of individuals attempting to set up and run projects within transboundary protected areas might be more fruitful. In order to do this, the paper engages with how individuals themselves define cooperation, and their own positions and roles within the complex process of institutional change, beyond easy clichés of handshakes and friendships. It focuses on the negotiated role of individuals and coordination structures as examples of the construction of individual and collective identities. Many examples of projects could have been used to discuss this. Here, extensive fieldwork carried out in five European transboundary protected areas is evoked to ground the discussion.